2020
DOI: 10.3390/ma13204632
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Composite Filaments Based on Polylactide and Diatomaceous Earth for 3D Printing

Abstract: New composites containing a natural filler made of diatom shells (frustules), permitting the modification of polylactide matrix, were produced by Fused Deposition Modelling (3D printing) and were thoroughly examined. Two mesh fractions of the filler were used, one of <40 µm and the other of 40−63 µm, in order to check the effect of the filler particle size on the composite properties. The composites obtained contained diatom shells in the concentrations from 0% to 5% wt. (0−27.5% vol.) and were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
4
17
0
Order By: Relevance
“…According to our previous research, for the species of diatoms used for this study, the particles smaller than 6 µm can be attributed to broken frustules (pieces thereof), while particles larger than approx. 40 µm are mostly agglomerates or colonies of frustules, as well as some single specimens of a bigger size [ 22 ]. It was observed that fraction 3 obtained by sedimentation of diatomaceous earth shows much narrower distribution of particle size, ranging from approx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our previous research, for the species of diatoms used for this study, the particles smaller than 6 µm can be attributed to broken frustules (pieces thereof), while particles larger than approx. 40 µm are mostly agglomerates or colonies of frustules, as well as some single specimens of a bigger size [ 22 ]. It was observed that fraction 3 obtained by sedimentation of diatomaceous earth shows much narrower distribution of particle size, ranging from approx.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed an additional band at a wavelength of 797 cm −1 , which is caused by symmetric bending vibrations of Si–O–Si bonds [ 27 ]. The band at 1646 cm −1 is due to bending vibrations of H–O–H bonds of bound molecular water [ 22 ]. We additionally observed bands at a wavelength of 1015 cm −1 , which could be attributed to the asymmetric stretching of Si–O–Si bond, while the 661 cm −1 belong to symmetric stretching [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to our previous research, for the species of diatoms used for this study, the particles smaller than 6 µm can be attributed to broken frustules (pieces thereof), while particles larger than approx. 40 µm are mostly agglomerates or colonies of frustules, as well as some single specimens of a bigger size [15].…”
Section: Particle Size Measurements By Dynamic Light Scattering (mentioning
confidence: 99%
“…Currently, two other groups of fixing materials are available for resorbable osteosynthesis in mandibular condylar fractures: polymers and metal alloys. Because of the promising chemical properties [ 20 ], a series of polylactide fixing materials [ 21 , 22 ] dedicated for that purpose (pins, screws, and meshes) have been developed in the last two decades. Their physical properties require some compromise in bone fragment fixation.…”
Section: Introductionmentioning
confidence: 99%